PENUNDAAN PEMBERANGKATAN JAMAAH HAJI INDONESIA TAHUN 2020 – 2021 PERSPEKTIF MASLAHAH - Akmalia, Husnul; Mustafa, Adriana (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar’iyyah, 2022)
This article is focused on examining the postponement of the departure of prospective pilgrims, especially in 2020 and 2021 as a result of the postponement of the hajj by the Saudi Arabian Government due to the Covid-19 pandemic. This research is a field qualitative research with juridical, normative syar’i, and sociological approaches. The results of this study show that the postponement of the implementation of the Hajj by the Saudi Arabian Government has an impact on the departure of prospective Indonesian pilgrims for 2 (two) consecutive years (2020 – 2021). The main reason for the delay was to maintain the safety of the souls of prospective pilgrims (hifz al-nafs), and this was in line with one of the rules in maqasid al sharia. Although it causes disappointment for prospective pilgrims, but in general the condition is understandable. In addition, the Ministry of Religious Affairs also provides an option for prospective pilgrims to withdraw the initial deposit and repayment of their Hajj savings, with the consequence that if what is withdrawn is the initial deposit fund, then the prospective pilgrim can no longer leave except for re-registration, while if what is withdrawn is the repayment fund, then the departure queue does not change as long as the repayment is made during the return to repayment when the hajj returns to normal.